Permasalahan Pembelajaran PAI dan Solusinya di SD 1 Peganjaran - Imalia Yoni (Al Hikmah: Journal of Education, 2020)
Islamic Religious education is a learning system that can prepare students to recognize, understand, appreciate, believe in, and be devoted to, based on the Qur’an and Hadits. The purpose of Islamic Education itself is to foster students to get closer to the creator of the universe and understand how great his power is and can carry out the teachings of Islam properly and perfectly, such as carrying out the obligations of every Muslim and stay away from his prohibitions. The scope of Islamic religious education is the knowledge of monotheism, the science of jurisprudence, Al-Qur’an, Hadits, Morals, and Islamic dates. In the Implementation, there are problems, various problems that are internal, or external. The solution offered to overcome the problems of Islamic education in schools is through a partial approach, optimizing the role of the affective domain and creating a religious climate in the educational environment.Pendidikan Agama Islam adalah sistem pembelajaran yang dapat mempersiapkan siswa untuk Mengenali, Memahami, Menghargai, Meyakini, dan Mengabdi, Berdasarkan Al-Qur’an dan HaditsTujuan dari Pendidikan Agama Islam  itu sendiri ialah mendolong siswa agar lebih dekat dengan Pencipta Alam semesta dan memahami betapa hebatnya kekuatannya dan dapat menjalankan ajaran agama islam dengan baikdan sempurna, seperti melaksanakan kewajiban setiap muslim dan menjauhi larangannya. Ruang Lingkup Pendidikan Agama Islamadalah pengetahuan tentang Ilmu Tauhid, Ilmu Fiqih, Al-Qur'an, Hadits, Akhlak, dan tanggal Islam. Dalam Impelemtasi ada Masalah, berbgai masalah yang bersifat Internal, atau Eksternal. Solusi yang ditawarkan untuk mengatasi masalah pendidikan Islam di sekolah adalah melalui pendekatan Parsial, Mengoptimalkan peran domain afektif dan menciptakan iklim keagamaan di Lingkungan Pendidikan.